Molecular dynamics simulation-guided drug sensitivity prediction for lung cancer with rare EGFR mutations - Ikemura, Shinnosuke; Yasuda, Hiroyuki; Matsumoto, Shingo; Kamada, Mayumi; Hamamoto, Junko; Masuzawa, Keita; Kobayashi, Keigo; Manabe, Tadashi; Arai, Daisuke; Nakachi, Ichiro; Kawada, Ichiro; Ishioka, Kota; et al. (Proceedings of the National Academy of Sciences - PNAS, 2019)
Next generation sequencing (NGS)-based tumor profiling identified an overwhelming number of uncharacterized somatic mutations, also known as variants of unknown significance (VUS). The therapeutic significance of mutations outside mutational hotspots, consisting of >50 types, in nonsmall cell lung carcinoma (NSCLC) is largely unknown. In fact, our pan-nation screening of NSCLC without hotspot mutations ( = 3,779) revealed that the majority (>90%) of cases with rare mutations, accounting for 5.5% of the cohort subjects, did not receive EGFR-tyrosine kinase inhibitors (TKIs) as a first-line treatment. To tackle this problem, we applied a molecular dynamics simulation-based model to predict the sensitivity of rare EGFR mutants to EGFR-TKIs. The model successfully predicted the diverse in vitro and in vivo sensitivities of exon 20 insertion mutants, including a singleton, to osimertinib, a third-generation EGFR-TKI ( = 0.72, = 0.0037). Additionally, our model showed a higher consistency with experimentally obtained sensitivity data than other prediction approaches, indicating its robustness in analyzing complex cancer mutations. Thus, the in silico prediction model will be a powerful tool in precision medicine for NSCLC patients carrying rare mutations in the clinical setting. Here, we propose an insight to overcome mutation diversity in lung cancer.